Synthesis, Characterization, and Flocculation Properties of Branched Cationic Polyacrylamide. (24th April 2013) - Sun, Weimin; Zhang, Guangcheng; Pan, Ling; Li, Helin; Shi, Aihua
Abstract : A water soluble branched cationic polyacrylamide (BCPAM) was synthesized using solution polymerization. The polymerization was initiated using potassium diperiodatocuprate, K5 [Cu(HIO6 )2 ](Cu(III)), initiating the self-condensing vinyl copolymerization of acrylamide and acryloxyethyltrimethyl ammonium chloride (DAC) monomer. The resulting copolymer was characterized by the use of Fourier-transform infrared (FTIR) spectroscopy and nuclear magnetic resonance (NMR) spectroscopy. Its flocculation properties were evaluated with standard jar tests of sewage. The effects of initiator concentration, monomer concentration, reaction temperature, and the mass ratio of monomers on intrinsic viscosity and flocculation properties of the product were determined using single-factor experiments and orthogonal experiment.